1962
DOI: 10.1042/bj0830291
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in the tissues of animals injected with iron. 3. Lipid peroxidation

Abstract: Vol. 83 GLUTAMINE METABOLISM IN CARCINOMA CELLS 291oxidation of glutamine results in the formation of aspartic acid. 2. In the presence of substances giving rise to acetyl-coenzyme A, the rate of oxidation of glutamine is decreased, but the extent of oxidation is increased.3. The rate of glutamine oxidation is increased by sodium hydrogen carbonate and a-oxo acids.4. The incorporation of amino acids into proteins is inhibited under anaerobic conditions by pyruvate, oxaloacetate and phenylpyruvate. This inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1967
1967
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In an animal model of acute iron overload, we have previously demonstrated that hydroxyl radical is generated and arises by the reduction of molecular oxygen to the hydroxyl radical via hydrogen peroxide without the requirement for pre-existing peroxides (26). Numerous studies and reviews on the pathology of chronic iron overload disorders suggested a role for ironinduced lipid peroxidation with consequent membrane damage, perhaps due to free radical formation (3,12,15,44). Apparently, hydroxyl radical does not participate in the initiation of lipid peroxidation (45).…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of acute iron overload, we have previously demonstrated that hydroxyl radical is generated and arises by the reduction of molecular oxygen to the hydroxyl radical via hydrogen peroxide without the requirement for pre-existing peroxides (26). Numerous studies and reviews on the pathology of chronic iron overload disorders suggested a role for ironinduced lipid peroxidation with consequent membrane damage, perhaps due to free radical formation (3,12,15,44). Apparently, hydroxyl radical does not participate in the initiation of lipid peroxidation (45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fibrogenic factor purified from the liver ofrats treated with thioacetamide or CC14 (12,16) may be the result of lipid peroxidation induced by these hepatotoxins. Because lipid peroxidation also occurs in unstimulated quiescent cultured fibroblasts (1 1, 17, 18), as well as in normal tissues in vivo (Houglum, K., unpublished observations; [19][20][21][22], we wondered if products of lipid peroxidation might modulate basal collagen gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of d-a-tocopherol (10-50 MM), BW755c (100 MM), Probucol (15 MM), propyl gallate (10 MM), and methylene blue (10 AM), a scavenger ofreducing equivalents (24), on quiescent cells was assessed by the addition of these compounds during the incubation period (20 h). After the incubation period, 0.2 mM ascorbic acid (a cofactor for prolyl and lysyl hydroxylases) and 20 MCi of L-[53H]proline were added and the incubation was continued for up to 4 h (23). Labeling of cells was terminated by cooling the plates to 0°C.…”
Section: Introductionmentioning
confidence: 99%
“…These are not mutually exclusive theories as lipid peroxidation may mediate the loss of lysosomal membrane integrity. Although ionic iron (Fe2+, Fe3+) in vitro can initiate lipid peroxidation in isolated hepatocellular organelles (11)(12)(13)(14)(15)(16)(17)(18), evidence that chronic iron overload results in hepatic lipid peroxidation in vivo has been limited to two reports in which increased malonic dialdehyde (MDA)l was demonstrated in liver of rats that had received parenteral iron dextran (19,20 Preparation of hepatic mitochondrial fraction. Experimental and control rats from each group were treated identically as above except that the homogenizing solution was 0.25 M sucrose, 0.003 M EDTA, pH 7.4.…”
mentioning
confidence: 99%